2006
DOI: 10.1634/stemcells.2005-0430
|View full text |Cite
|
Sign up to set email alerts
|

Progenitors Systemically Transplanted into Neonatal Mice Localize to Areas of Active Bone Formation In Vivo: Implications of Cell Therapy for Skeletal Diseases

Abstract: The potential of cell or gene therapy to treat skeletal diseases was evaluated through analysis of transplanted osteoprogenitors into neonatal homozygous and heterozygous osteogenesis imperfecta mice (oim). The osteoprogenitors used for transplantation were prepared by injection of mesenchymal stem cells (MSCs) marked with the green fluorescent protein (GFP) into normal mice with the subsequent retrieval of the cells at 35 days. The retrieved cells referred to here as osteoprogenitors were expanded in culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 49 publications
(64 reference statements)
2
51
0
Order By: Relevance
“…Transplanted e-CSC homed to areas of bone growth and fracture repair and expressed osteoblast differentiation genes Osteopontin and Osteocalcin and the COL1A2 protein, indicating their differentiation to functional osteoblasts. These findings are in agreement with previous studies in the oim model that demonstrated the direct differentiation of transplanted cells to osteoblasts [13][14][15][16] and subsequent improvements in disease pathology. In addition, we used the detection of human factor IX as an immunoassay to detect the presence of mouse anti-human antibodies in the serum of mice transplanted with human cells and we were able to show the absence of immune reaction against allogeneic cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Transplanted e-CSC homed to areas of bone growth and fracture repair and expressed osteoblast differentiation genes Osteopontin and Osteocalcin and the COL1A2 protein, indicating their differentiation to functional osteoblasts. These findings are in agreement with previous studies in the oim model that demonstrated the direct differentiation of transplanted cells to osteoblasts [13][14][15][16] and subsequent improvements in disease pathology. In addition, we used the detection of human factor IX as an immunoassay to detect the presence of mouse anti-human antibodies in the serum of mice transplanted with human cells and we were able to show the absence of immune reaction against allogeneic cells.…”
Section: Discussionsupporting
confidence: 93%
“…In humans, whole bone marrow and bone marrow mesenchymal stem cells (MSC) have been transplanted in OI children with gains in body length and bone mineralization [8,9], while allogeneic fetal liver-derived stem cells transplanted in utero led to apparent phenotypic improvement in an OI fetus, although confounded by concomitant bisphosphonate use [10]. In rodent OI models, transplantation of whole bone marrow/bone marrow MSC led to increased collagen content [11], improved bone strength, reduced perinatal lethality [12], and increased osteoblast differentiation [13,14]. Marked therapeutic benefits were shown following transplantation of fetal MSC from human first trimester blood in a mouse model of human type III OI (oim) including improved bone plasticity and a two-third reduction in long bone fractures [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] The primary goal of this work was to define the approach, develop the means, and set the stage for future studies of different treatment aspects. Our observations of (1) a major fraction of bone matrix synthesized by a minor fraction of engrafted osteoblasts, (2) recovery of bone quality in treated mice, and (3) rescue of the lethal phenotype address some existing puzzles and offer insights for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…16 Unfortunately, most animal studies were limited to the treatment of oim mice with virally transduced cells. [15][16][17] Viral transduction may alter the differentiation, proliferation, and function of transplanted cells in vivo. 18 In addition, the oim mouse itself is a model of a rare, recessive form of OI with only one known patient.…”
Section: Introductionmentioning
confidence: 99%
“…Extension of this example to the unique cartilaginous tissue of the IVD could be the most accessible and safest application of stem cell biology to the disease processes treated by neurological surgeons. 26 …”
Section: In Vitro Msc Fate Determination and The Role Of The Microenvmentioning
confidence: 99%